Description of Radiation Damage in Diamond Sensors Using an Effective Defect Model. Issue 11 (17th August 2017) - Kassel, Florian; Guthoff, Moritz; Dabrowski, Anne; de Boer, Wim
Abstract : The Beam Condition Monitoring Leakage (BCML) system is a beam monitoring device in the CMS experiment at the LHC consisting of 32 poly‐crystalline (pCVD) diamond sensors. The BCML sensors, located in rings around the beam, are exposed to high particle rates originating from the colliding beams. These particles cause lattice defects, which act as traps for the ionized charge carrier leading to a reduced charge collection efficiency (CCE). The radiation induced CCE degradation was, however, much more severe than expected from low rate laboratory measurements. Measurement and simulations presented in this paper show that this discrepancy is related to the rate of incident particles. At high particle rates, the trapping rate of the ionization is strongly increased compared to the detrapping rate leading to an increased build‐up of space charge. This space charge locally reduces the internal electric field increasing the trapping rate and hence reducing the CCE even further. In order to connect these macroscopic measurements with the microscopic defects acting as traps for the ionization charge, the TCAD simulation program SILVACO was used. It allows to introduce the defects as effective donor and acceptor levels, and can calculate the electric field from Transient Current Technique (TCT) signals and CCE as a function of the effective trap properties, like density, energy level, and trapping cross section. After each irradiation step, these properties were fitted to the data on the electric field from the TCT signals and CCE. Two effective acceptor and donor levels were needed to fit the data after each step. It turned out that the energy levels and cross sections could be kept constant and the trap density was proportional to the cumulative fluence of the irradiation steps. The highly non‐linear rate dependent diamond polarization and the resulting signal loss can be simulated using this effective defect model and is in agreement with the measurement results. Abstract : The radiation induced CCE degradation of the diamond based BCML detector at CMS was much more severe than expected from low rate laboratory measurements. A new effective defect model was developed, which is in agreement with the measurement results explaining the highly non‐linear rate dependent diamond polarization and the resulting signal loss.